Methods for Extracting Immune-Response Modulating Agents of Plant Origin - Oksana V. Kozlova; Natalia S. Velichkovich; Elizaveta R. Faskhutdinova; Olga A. Neverova; Andrey N. Petrov (Техника и технология пищевых производств)
Numerous adverse factors may violate the human immune system and trigger various diseases. Immune-response modulating agents, or immunomodulators, help the immune system to function properly. Biologically active substances extracted from medicinal plants are especially promising in this respect. The article reviews traditional and novel methods for extracting biologically active immune-response modulating agents from plant raw materials. The review covered articles published in English and Russian in 2019–2023 and indexed in Scopus, Web of Science, and eLIBRARY. Extraction efficiency depends on such factors as solvent, temperature, and particle size, but the method is the most important one. Traditional extraction methods include percolation, maceration, Soxhlet extraction, heat reflux extraction, and decoction. However, they are solvent-consuming and expensive. Modern extraction methods rely on carbon dioxide, microwave treatment, ultrasonic processing, and pressure. They proved quite efficient in extracting biologically active substances from ginseng (Panax gin- seng). Carbon dioxide, or supercritical, extraction was able to isolate polyphenol quercetin from quince fruit (Cydonia oblonga) and other biologically active substances from alfalfa (Medicago sativa). Maceration with methanol was applied to meadowsweet (Filipendula ulmaria) while Soxhlet extraction proved especially effective with smoke tree (Cotinus coggygria), moorland spotted orchid (Dactylorhiza maculata), and greater butterfly-orchid (Platanthera chlorantha). Both traditional and novel extraction methods find their application in medicine and food science, where they yield plant extracts of biologically active immune-response modulating agents.